4(k+3)=28*

Simple and best practice solution for 4(k+3)=28* equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(k+3)=28* equation:



4(k+3)=28*
We move all terms to the left:
4(k+3)-(28*)=0
We add all the numbers together, and all the variables
4(k+3)-0=0
We add all the numbers together, and all the variables
4(k+3)=0
We multiply parentheses
4k+12=0
We move all terms containing k to the left, all other terms to the right
4k=-12
k=-12/4
k=-3

See similar equations:

| (X-5)=(x-5) | | 2.65-3y=7.25 | | -4.9t^2+8t+450=0 | | Y-4=-2(x5) | | 100+20c=1,140 | | 3d-3.4=2.2 | | -34+4x=7(5x+4) | | 5x+87=10x+17 | | V-7=6v-2 | | 6y+2=-3y-7 | | (X^2)y=4 | | 45y+43=25y+6 | | X^2*y=4 | | 4=5k-3k | | (2y/700)*700=0 | | 4(y+3)-7=5 | | 15x-7=-68 | | 0=5d+10d | | -1/8=x/2 | | 2r^2+3r+9=5 | | 2x+-12=x-6 | | n—21/2=71/2 | | 4y+5=47-8 | | n–21/2=71/2 | | 9x-25=16x+5 | | 4n-8/8=5 | | 1/8=126x | | 5^(-2x+1)-(1/25)^x=x^2*25^x | | 5/6x=50/21 | | -3x2=27 | | 14x^2-3x+2=9x^2-11x+6 | | 2/8=3x |

Equations solver categories